China's Trade Relations with US and the EU: WTO Membership, Free Markets (?), Agricultural Subsidies and Clothing, Textile and Footwear Qoutas - Kate Hannan (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2006)
This paper discusses three scenarios concerning China's recent trade negotiations and relations with the United States and the European Union. Chinese commentators and academics are sure that their country 'is firmly on the path of greater integration with the global economy' and that this is 'a path that has provided great benefits for China and for the world in general. However, they are also be well aware of the problems associated with entering a global economy where free trade/level playing field market principles have not ended either agricultural subsidies or import quotas on manufactured goods. Indeed, as argued in this paper, measures taken in the name of neo-liberal free market ideals have, ironically, spawned an ever-growing mass of quotas imposed by the EU and the US on the importation of Chinese clothing, footwear and textiles. Keywords: China, subsidiaries, WTO, USA, EU
hdl:10398/7398
Keywords: 330; china; kina; usa; eu; wto; international handel